Designing Dual Transglutaminase 2/Histone Deacetylase Inhibitors Effective at Halting Neuronal Death. (18th January 2018) - Basso, Manuela; Chen, Huan Huan; Tripathy, Debasmita; Conte, Mariarosaria; Apperley, Kim Y. P.; De Simone, Angela; Keillor, Jeffrey W.; Ratan, Rajiv; Nebbioso, Angela; Sarno, Federica; Altucci, Lucia; Milelli, Andrea
Abstract: In recent years there has been a clear consensus that neurodegenerative conditions can be better treated through concurrent modulation of different targets. Herein we report that combined inhibition of transglutaminase 2 (TG2) and histone deacetylases (HDACs) synergistically protects against toxic stimuli mediated by glutamate. Based on these findings, we designed and synthesized a series of novel dual TG2–HDAC binding agents. Compound3 [( E )‐ N ‐hydroxy‐5‐(3‐(4‐(3‐oxo‐3‐(pyridin‐3‐yl)prop‐1‐en‐1‐yl)phenyl)thioureido)pentanamide] emerged as the most interesting of the series, being able to inhibit TG2 and HDACs both in vitro (TG2 IC50 =13.3±1.5 μm, HDAC1 IC50 =3.38±0.14 μm, HDAC6 IC50 =4.10±0.13 μm ) and in cell‐based assays. Furthermore, compound3 does not exert any toxic effects in cortical neurons up to 50 μm and protects neurons against toxic insults induced by glutamate (5 mm ) with an EC50 value of 3.7±0.5 μm . Abstract : Many hands make light work : We discovered that concomitant inhibition of histone deacetylase (HDAC) and transglutaminase 2 (TG2) synergistically protects cortical neurons from toxic stimuli induced by glutamate. Based on this finding, we have developed a new class of multiple ligands that are able to modulate both targets. Compound3 inhibits both targets in vitro and in cells, and is effective in halting oxidative stress‐mediated neuronal death.